CHEMICAL CHARACTERISTICS OF METAL PHASES OF THE RICHARDTON H5 CHONDRITE - Kong P.; Ebihara M.; Nakahara H.; Endo K. (My University, 1995)
The magnetic fraction was separated from the Richardton H5 chondrite with a hand magnet and was leached with concentrated HF at high temperature for different periods. The resulting metallic fractions and the untreated magnetic fraction were analyzed using Mossbauer spectroscopy and instrumental neutron activation analysis (INAA). Leaching in concentrated HF for 1.5-5 min was effective in removing silicates from the magnetic fraction while leaving the metal grains intact. Leaching with increasing time selectively dissolved kamacite, with only little attack of the taenite grains. The Mossbauer spectroscopy shows that martensite (α-phase iron) is present in the Richardton metals and is dissolved in HF less easily than kamacite, but more easily than taenite.The distributions of trace siderophile elements among the different metal phases of Richardton were obtained based on the INAA data. Siderophile elements, except for Co, are enriched in the taenite fraction but with different concentration ratios between taenite and kamacite, suggesting that kamacite and taenite were not formed by either oxidation/reduction of Fe of the Fe-Ni metal, or by condensation from the nebula, or by metal-solid differentiation. A more likely explanation is that kamacite and taenite have equilibrated by low-temperature diffusion. It seems that most trace siderophile elements were once dissolved in the Fe-Ni metal and later distributed among the metal phases by diffusion. However, Ir, Os and Ru may still partly exist as tiny separate grains in the FeNi metal and their distributions among the metal phases are not completely equilibrated.